Hubungan Persepsi Pasien tentang Tenaga Kesehatan dalam Memberikan Pelayanan Kesehatan dengan Kepuasan Pasien di Puskesmas Citeureup: Hubungan Persepsi Pasien tentang Tenaga Kesehatan dalam Memberikan Pelayanan Kesehatan dengan Kepuasan Pasien di Puskesmas Citeureup - rahmah oktaviani, nurul; Setiawati, Setiawati; Rohayani, Lilis (JURNAL KESEHATAN KARTIKA, 2025)
Background: Health services are services provided both to prevent and treat, including 9 component elements and patient satisfaction is the level of patient feelings that arise as a result of unexpected performance consisting of 5 dimensions, there are 4 dimensions that are problematic in this research, including tangibility, reliability, responsiveness, assurance. Poor service will have an impact on patient satisfaction according to data from the Cimahi City Health Service regarding a community satisfaction survey regarding community health center services in 2024, the highest score was at the Cigugur Tengah Health Center (84.32) and the lowest score was at the Citeureup Community Health Center (80.04). Objective: This study aims to determine the relationship between patient perceptions of health workers in providing health services and patient satisfaction at the Citeureup Community Health Center. Method: Type of research is quantitative with an analytical survey research design in this research method using a cross sectional design. The total sample was 91 people using purposive sampling technique, there were inclusion and exclusion criteria. Data collection uses a questionnaire. Data analysis was carried out, namely univariate and bivariate (Chi-Square). Results: Based on the results of the univariate analysis, it can be seen that 42 people (46.2%) felt the service was poor and 42 people (46.2%) felt less satisfied. Chi-Square test results show that there is a relationship between health services and patient satisfaction with a P value of 0.00 <0.05. Conclusion: There is a relationship between patient perceptions about health workers in providing health services and patient satisfaction.  Suggestions for community health centers can be equipped with facilities such as waiting chairs, wheelchairs and crutches and suggestions for future researchers are expected to research "Factors that influence health services.